Peningkatan Kompetensi Auditor Internal PT PLN Nusantara Power melalui Pengabdian Masyarakat dengan Tema In-House Training ISO 19011:2018 dan Workshop Audit Internal PLN NP-IMS - Rio Afrianda (Universitas Dirgantara Marsekal Suryadarma, 2026)
The implementation of the PLN Nusantara Power Integrated Management System (PLN NP-IMS) requires competent internal auditors in accordance with ISO 19011:2018 to ensure effective management system auditing and continual improvement. A needs assessment identified gaps in auditors' competencies, particularly in risk-based auditing, audit program development, evidence collection, audit reporting, and follow-up of audit findings. This community service program aimed to enhance the knowledge and practical skills of PT PLN Nusantara Power employees through an In-House Training on ISO 19011:2018 and an Internal Audit Workshop for PLN NP-IMS. The program adopted a Participatory Learning and Action (PLA) approach combining lectures, interactive discussions, case studies, workshops, and audit simulations. Program effectiveness was evaluated using pre-tests, post-tests, competency observations, and participant satisfaction questionnaires. The results showed that the average participant score increased from 64.8 to 88.6, representing an improvement of 23.8 points. The average competency observation score reached 4.43 (good category), while participant satisfaction achieved 4.87 (excellent category). Beyond improving individual competencies, the program established a shared understanding of internal audit practices and strengthened the implementation of PLN NP-IMS. These findings demonstrate that the training approach was effective in enhancing internal auditor competency and supporting the implementation of an integrated management system within PT PLN Nusantara Power.